(untitled) (Philological Studies, 2019)
In this essay, Koteska, analyses Kristeva’s psychoanalytic theory that the newly born child is gaining its "idea" of its own subjectivity via the fragmentation of the maternal body. After analyzing the outcomes of this theory in a lot of cultural images of an incomplete woman from poetry and paintings through movies and theoretical texts, she uses the absurd logics behind the very same psychoanalytic theory and turns it around, eventually proving this theory to be wrong. In other words, the text "Women without teeth" proves that there is no theoretical ground for the image of an "incomplete woman", frequently used and misused, in the patriarchy.